Are cervical and breast cancer screening programmes equitable? The case of women with intellectual and developmental disabilities. (19th March 2013) - Cobigo, V.; Ouellette‐Kuntz, H.; Balogh, R.; Leung, F.; Lin, E.; Lunsky, Y.
Abstract Background Effective cancer screening must be available for all eligible individuals without discrimination. Lower rates of cervical and breast cancer screening have been reported in certain groups compared with women from the general population, such as women with intellectual and developmental disabilities (IDD). Research on the factors explaining those observed differences is crucial to determine whether practices are unfair and could be improved. The aim of this population‐based study was to describe cancer screening utilisation by women with IDD in Ontario, Canada compared with other women in Ontario. The specific objectives were (1) to estimate the rates of cervical and breast cancer screening among eligible women with IDD in Ontario; (2) to compare the rates of cervical and breast cancer screening between eligible women with and without IDD; and (3) to examine if any observed differences between women with and without IDD persist after factors such as age, socio‐economic status, rurality and healthcare utilisation are accounted for. Method This study draws women with IDD from an entire population, and draws a randomly selected comparison group from the same population. It controls for important confounders in cancer screening within the limitations of the data sources. The study was conducted using health administrative databases and registries in Ontario, Canada. Two cohorts were created: a cohort of all women identified as having an IDD and a cohort consisting of a random sample of 20% of the women without IDD. Results The proportion of women with IDD who are not screened for cervical cancer is nearly twice what it is in the women without IDD, and 1.5 times what it is for mammography. Conclusions Findings suggest that women with IDD experience inequities in their access to cancer screening. Public health interventions targeting this population should be implemented.